National Insecurity and Human Rights : Democracies Debate Counterterrorism. - Alison, Brysk (Global, Area, & International Archive., 2003)
Human rights is all too often the first casualty of national insecurity. How can democracies cope with the threat of terror while protecting human rights? This volume compares the lessons of the United States and Israel with the 'best-case scenarios' of the United Kingdom, Canada, Spain, and Germany.